Carbon quantum dots, modified activated carbon, preparation method and application thereof

Carbon quantum dots are prepared by using eutectic solvents prepared by amide compounds and transition metal compounds, and used to modify activated carbon, which solves the problem of insufficient thermal stability and adsorption performance of activated carbon when treating CVOCs, and achieves high efficiency , safe CVOCs adsorption effect.

CN117602613BActive Publication Date: 2025-02-14CHINA UNIV OF PETROLEUM (BEIJING) +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311370056.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-02-14
Estimated Expiration
2043-10-20

AI Technical Summary

Technical Problem

The existing activated carbon has poor thermal stability, a risk of combustion and depletion and insufficient adsorption performance when treating industrial halogenated organic volatiles (CVOCs). The modification method has problems such as environmental pollution, high complexity and high cost.

Method used

Carbon quantum dots were prepared by using amide compounds and transition metal compounds as precursors, and carbon quantum dots were prepared by microwave heating and used for modified activated carbon to enhance its adsorption performance and thermal stability.

Benefits of technology

It significantly improves the adsorption performance and chemical stability of modified activated carbon, reduces the risk of combustion and explosion, and has a simple process, low cost and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117602613B_ABST
    Figure CN117602613B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of gas treatment technology, and specifically discloses a carbon quantum dot, modified activated carbon, and a preparation method and application. The carbon quantum dots are prepared by microwave heating using a low eutectic solvent as a precursor; the low eutectic solvent is prepared from an amide compound and a transition metal compound with a molar ratio of 6:1 to 1:2; the amide compound is a C4 to C18 aliphatic amide, and the transition metal compound is an oxide or salt of Fe, Ni or Co. The preparation method of the modified activated carbon is: the carbon quantum dot solution is roasted with an activated carbon raw material. The activated carbon preparation process of the present invention is easy to operate, green and environmentally friendly, can be used for industrial halogenated volatile organic compounds (CVOCs) waste gas adsorption, has the characteristics of high adsorption capacity and strong selectivity, and has broad application prospects in the field of CVOCs treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas treatment, and in particular to carbon quantum dots, modified activated carbon, and a preparation method and application thereof. Background Art

[0002] Industrial halogenated organic volatiles (CVOCs) have strong bioaccumulation, high toxicity and resistance to degradation. How to efficiently deal with CVOCs has become a global concern. At present, the main methods for treating CVOCs include condensation, absorption, adsorption, catalytic combustion, and biology. Among them, adsorption is still the most widely used method for treating CVOCs.

[0003] Activated carbon adsorption is widely used in the removal of CVOCs waste gas in industrial production processes due to its advantages such as low cost, simple operation process, and easy automation control. However, activated carbon has poor thermal stability and potential explosion hazards. There is a certain fire risk in the actual application process, which has caused many explosion accidents, seriously endangering the safety of the entire production process, and greatly limiting its application in industry. In addition, the adsorption performance of activated carbon needs to be further improved. In order to solve the above-mentioned defects in the application of activated carbon, it is currently mainly modified by physical and chemical methods. However, the current modifiers mainly include strong acids, strong bases, etc., which generally have problems such as large environmental pollution, complex modification methods, high costs, and poor modification effects. The adsorption amount of CVOCs by modified activated carbon is not ideal. Therefore, it is of great significance to develop an activated carbon adsorbent that has both excellent adsorption performance and high safety. Summary of the invention

[0004] In view of the problems existing in the prior art of modified activated carbon modification process, such as large environmental pollution, complex process, adsorption performance needs to be further improved, and potential safety hazards, the present invention provides a carbon quantum dot, modified activated carbon, preparation method and application.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0006] A carbon quantum dot is prepared by microwave heating using a low eutectic solvent prepared from an amide compound and a transition metal compound as a precursor;

[0007] Wherein, the molar ratio of the amide compound to the transition metal compound is 6:1 to 1:2;

[0008] The amide compound is a C4-C18 aliphatic amide; the transition metal compound is an oxide or salt of Fe, Ni or Co.

[0009] Compared with the prior art, the carbon quantum dots provided by the present invention use a low eutectic solvent prepared from an amide compound and a transition metal compound as a raw material, wherein the amide group in the amide compound can form a stable structure with the transition metal compound under the action of hydrogen bonding. The carbon quantum dots prepared from the precursor have abundant amide groups and highly reactive transition metal ions, which can significantly improve the adsorption performance of carbon quantum dots modified activated carbon. In addition, it can also effectively improve the thermal stability of activated carbon, reduce the possibility of explosion during the adsorption of CVOCs by activated carbon, and thus improve the safety of modified activated carbon.

[0010] Preferably, the amide compound is at least one of fumaramide, N,N-diethyllauramide or N-[3-(dimethylamino)propyl]lauramide; and / or

[0011] Preferably, the transition metal compound is at least one of ferric chloride hexahydrate, ferric oxide, nickel chloride hexahydrate, nickel oxide, cobalt chloride hexahydrate or cobalt monoxide.

[0012] Preferably, the method for preparing the low eutectic solvent is: uniformly mixing the amide compound and the transition metal compound, heating to 50° C. to 120° C., and maintaining the temperature until the system is uniform and transparent, thereby obtaining the low eutectic solvent.

[0013] The present invention also provides a method for preparing carbon quantum dots, comprising the following steps: subjecting the low eutectic solvent to microwave heating reaction to obtain a carbon quantum dot solution.

[0014] Furthermore, the microwave heating reaction has a power of 500W to 800W, a temperature of 50°C to 70°C, and a time of 3min to 8min.

[0015] The present invention also provides a modified activated carbon, comprising the carbon quantum dots and activated carbon.

[0016] The present invention also provides a method for preparing modified activated carbon, comprising the following steps: uniformly mixing activated carbon raw materials and carbon quantum dot solution, and calcining under an inert atmosphere to obtain modified activated carbon.

[0017] Furthermore, the calcination temperature is 600° C. to 1000° C., and the calcination time is 1 h to 4 h.

[0018] Furthermore, the mass-to-volume ratio of the activated carbon raw material to the carbon quantum dot solution is 5-20:100, wherein the unit of mass is gram and the unit of volume is milliliter.

[0019] Preferably, the activated carbon raw material is fly ash residue obtained after acid leaching and impurity removal of fly ash from a coal-fired power plant.

[0020] More preferably, the method for preparing the activated carbon raw material comprises the following steps: the method for preparing the activated carbon raw material comprises the following steps: adding fly ash from a coal-fired power plant into a mixed acid solution, dispersing it evenly, immersing it at 120°C to 130°C for 3h to 6h, filtering, washing the filter residue, and drying to obtain the activated carbon raw material.

[0021] Furthermore, the mixed acid solution is a mixed solution of nitric acid solution and phosphoric acid solution in a molar ratio of 1:2-4.

[0022] Specifically, the mass concentration of nitric acid in the mixed acid solution is 60% to 70%, and the mass concentration of phosphoric acid is 80% to 90%.

[0023] Furthermore, the solid-to-liquid ratio of the fly ash from the coal-fired power plant to the mixed acid solution is 1g:8-12mL.

[0024] Preferably, the immersion temperature is 120° C. and the immersion time is 5 h.

[0025] The preparation method of modified activated carbon provided by the present invention uses industrial solid waste as the activated carbon raw material, and modifies the activated carbon by carbon quantum dots prepared by a specific low eutectic solvent, which significantly improves the adsorption performance and chemical stability of the modified activated carbon. The preparation process is simple, easy to operate, low in cost, low in toxicity and environmentally friendly. It is a low-cost, eco-friendly and resource-saving preparation method with broad application prospects.

[0026] The present invention also provides the use of the modified activated carbon described in any one of the above items, or the modified activated carbon prepared by the preparation method of the carbon oxide quantum dot / sepiolite composite material described in any one of the above items in the adsorption of CVOCs. The activated carbon adsorption of CVOCs vapor experiment was carried out using an online adsorption device.

[0027] Exemplarily, CVOCs target chloroform as a pollutant.

[0028] The low eutectic solvent provided by the present invention is used as a precursor to prepare carbon quantum dots, and the activated carbon is modified by the carbon quantum dots. The carbon quantum dots are stably and evenly attached to the pore structure of the activated carbon through the various functional groups on the surface of the carbon quantum dots, which increases the adsorption sites of the activated carbon, thereby significantly increasing the adsorption capacity of the activated carbon. Furthermore, the selective adsorption performance of the activated carbon for CVOCs is enhanced through the amide groups and transition metal ions in the amide groups, thereby achieving high capacity and selective adsorption of CVOCs by the activated carbon. In addition, the present invention uses industrial solid waste as the activated carbon raw material, realizes the resource utilization of industrial waste, and is a green, environmentally friendly, and eco-friendly CVOCs adsorbent, which has a high application prospect in the treatment of CVOCs by adsorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1The scanning electron microscope images of the original activated carbon and the modified activated carbon in Example 3 of the present invention, wherein (a) the original activated carbon, (b) the modified activated carbon; DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0031] In order to better illustrate the present invention, further examples are given below.

[0032] Example 1

[0033] The embodiments of the present invention provide a carbon quantum dot and a modified activated carbon.

[0034] The carbon quantum dots are prepared by microwave reaction using a low eutectic solvent prepared from fumaramide and ferric chloride hexahydrate in a molar ratio of 4:1 as a precursor, and specifically comprising the following steps:

[0035] 0.04 mol (4.56 g) of fumaramide and 0.01 mol (2.70 g) of ferric chloride hexahydrate were placed in a round-bottom flask, placed in an 80°C oil bath, and stirred with a magnetic stirrer for 2 h. The system was homogeneous and transparent, and a low eutectic solvent was obtained.

[0036] The low eutectic solvent was subjected to microwave heating at 500 W and 50° C. for 5 min to obtain a carbon quantum dot solution.

[0037] The method for preparing modified activated carbon using the above carbon quantum dots specifically comprises the following steps:

[0038] Step a, adding fly ash from a coal-fired power plant into a mixed acid solution of nitric acid and phosphoric acid in a molar ratio of 1:3, with a solid-liquid ratio of 1 g:10 mL, dispersing evenly, immersing at 120° C. for 3 h, filtering, washing the filter residue until the pH of the washing solution is 6-7, and drying to obtain an activated carbon raw material;

[0039] The mass concentration of nitric acid in the mixed acid solution is 68%, and the mass concentration of phosphoric acid is 85%;

[0040] Step b, mixing the above 100 mL carbon quantum dot solution with 10 g of the activated carbon raw material prepared in step a, placing them in a tubular furnace, heating to 850° C. under a nitrogen atmosphere, roasting for 1 hour, purging with nitrogen for 25 minutes, and cooling to room temperature to obtain modified activated carbon.

[0041] Example 2

[0042] The embodiments of the present invention provide a carbon quantum dot and a modified activated carbon.

[0043] The carbon quantum dots are prepared by microwave reaction using a low co-solvent prepared from N,N-diethyl lauramide and nickel chloride hexahydrate in a molar ratio of 6:1 as a precursor, and specifically comprising the following steps:

[0044] 0.06 mol (15.33 g) of N,N-diethyl lauramide and 0.01 mol (2.38 g) of nickel chloride hexahydrate were placed in a round-bottom flask, placed in a 70°C oil bath, and reacted with magnetic stirring for 2.5 hours. The system was homogeneous and transparent, and a low eutectic solvent was obtained;

[0045] The low eutectic solvent was subjected to microwave heating at 600 W and 60° C. for 5 min to obtain a carbon quantum dot solution.

[0046] The method for preparing modified activated carbon using the above carbon quantum dots specifically comprises the following steps:

[0047] Step a, adding fly ash from a coal-fired power plant into a mixed acid solution of nitric acid and phosphoric acid in a molar ratio of 1:3, with a solid-liquid ratio of 1 g:10 mL, dispersing evenly, immersing at 120° C. for 5 hours, filtering, washing the filter residue until the pH of the washing solution is 6-7, and drying to obtain an activated carbon raw material; the mass concentration of nitric acid in the mixed acid solution is 68%, and the mass concentration of phosphoric acid is 85%;

[0048] Step b, mix the above 100 mL carbon quantum dot solution with 5 g of the activated carbon raw material prepared in step a, put them into a tubular furnace, heat to 750° C. under a nitrogen atmosphere, roast for 1.5 h, purge with nitrogen for 20 min, and cool to room temperature to obtain modified activated carbon.

[0049] Example 3

[0050] The embodiments of the present invention provide a carbon quantum dot and a modified activated carbon.

[0051] The carbon quantum dots are prepared by microwave reaction using a low eutectic solvent prepared from N-[3-(dimethylamino)propyl]lauramide and cobalt chloride hexahydrate in a molar ratio of 2:1 as a precursor, specifically comprising the following steps:

[0052] 0.02 mol (5.69 g) of N-[3-(dimethylamino)propyl]lauramide and 0.01 mol (2.38 g) of cobalt chloride hexahydrate were placed in a round-bottom flask, placed in a 90°C oil bath, and reacted with magnetic stirring for 2 h. The system was homogeneous and transparent, and a low eutectic solvent was obtained;

[0053] The low eutectic solvent was subjected to microwave heating at 800 W and 70° C. for 3 min to obtain a carbon quantum dot solution.

[0054] The method for preparing modified activated carbon using the above carbon quantum dots specifically comprises the following steps:

[0055] Step a, adding fly ash from a coal-fired power plant into a mixed acid solution of nitric acid and phosphoric acid in a molar ratio of 1:3, with a solid-liquid ratio of 1 g:10 mL, dispersing evenly, immersing at 120° C. for 5 h, filtering, washing the filter residue until the pH of the washing solution is 6-7, and drying to obtain an activated carbon raw material;

[0056] The mass concentration of nitric acid in the mixed acid solution is 68%, and the mass concentration of phosphoric acid is 85%;

[0057] Step b, mix the above 100 mL carbon quantum dot solution with 15 g of the activated carbon raw material prepared in step a, put them into a tubular furnace, heat to 600° C. under a nitrogen atmosphere, roast for 1.5 h, purge with nitrogen for 20 min, and cool to room temperature to obtain modified activated carbon.

[0058] Example 4

[0059] The embodiments of the present invention provide a carbon quantum dot and a modified activated carbon.

[0060] The carbon quantum dots are prepared by microwave reaction using a low eutectic solvent prepared from N,N-diethyl lauramide and nickel oxide in a molar ratio of 1:1 as a precursor, specifically comprising the following steps:

[0061] 0.02 mol (5.11 g) of N,N-diethyl lauramide and 0.02 mol (1.49 g) of nickel oxide were placed in a round-bottom flask, placed in an oil bath at 100°C, and reacted for 1.5 h with magnetic stirring. The system was homogeneous and transparent, and a low eutectic solvent was obtained.

[0062] The low eutectic solvent was subjected to microwave heating at 700 W and 55° C. for 4 min to obtain a carbon quantum dot solution.

[0063] The method for preparing modified activated carbon using the above-mentioned deep eutectic solvent specifically comprises the following steps:

[0064] Step a, adding fly ash from a coal-fired power plant into a mixed acid solution of nitric acid and phosphoric acid in a molar ratio of 1:3, with a solid-liquid ratio of 1 g:10 mL, dispersing evenly, immersing at 120° C. for 5 hours, filtering, washing the filter residue until the pH of the washing solution is 6-7, and drying to obtain an activated carbon raw material; the mass concentration of nitric acid in the mixed acid solution is 68%, and the mass concentration of phosphoric acid is 85%;

[0065] Step b, mixing the above 100 mL carbon quantum dot solution with 20 g of the activated carbon raw material prepared in step a, placing them in a tubular furnace, heating to 950° C. under a nitrogen atmosphere, roasting for 4 h, nitrogen purging for 35 min, and cooling to room temperature to obtain modified activated carbon.

[0066] Example 5

[0067] The embodiments of the present invention provide a carbon quantum dot and a modified activated carbon.

[0068] The carbon quantum dots are prepared by microwave reaction using a low eutectic solvent prepared from fumaramide and cobalt monoxide in a molar ratio of 1:2 as a precursor, and specifically comprising the following steps:

[0069] 0.01 mol (1.14 g) of fumaramide and 0.02 mol (1.50 g) of cobalt monoxide were placed in a round-bottom flask, placed in an oil bath at 120°C, and reacted with magnetic stirring for 1 h. The system was homogeneous and transparent, and a low eutectic solvent was obtained.

[0070] The low eutectic solvent was heated in a microwave at 650 W and 65° C. for 6 min to obtain a carbon quantum dot solution.

[0071] The method for preparing modified activated carbon using the above carbon quantum dots specifically comprises the following steps:

[0072] Step a, adding fly ash from a coal-fired power plant into a mixed acid solution of nitric acid and phosphoric acid in a molar ratio of 1:3, with a solid-liquid ratio of 1 g:10 mL, dispersing evenly, immersing at 120° C. for 5 hours, filtering, washing the filter residue until the pH of the washing solution is 6-7, and drying to obtain an activated carbon raw material; the mass concentration of nitric acid in the mixed acid solution is 68%, and the mass concentration of phosphoric acid is 85%;

[0073] Step b, mixing the above 100 mL carbon quantum dot solution with 20 g of the activated carbon raw material prepared in step a, putting them into a tubular furnace, heating to 1000° C. under a nitrogen atmosphere, roasting for 1.5 h, nitrogen purging for 35 min, and cooling to room temperature to obtain modified activated carbon.

[0074] Example 6

[0075] The embodiments of the present invention provide a carbon quantum dot and a modified activated carbon.

[0076] The carbon quantum dots are prepared by microwave reaction using a low eutectic solvent prepared from N-[3-(dimethylamino)propyl]lauramide and ferric oxide in a molar ratio of 2:1 as a precursor, specifically comprising the following steps:

[0077] 0.02 mol (5.69 g) of N-[3-(dimethylamino)propyl]lauramide and 0.01 mol (1.60 g) of ferric oxide were placed in a round-bottom flask, placed in an oil bath at 110°C, and reacted with magnetic stirring for 1.5 h. The system was homogeneous and transparent, and a low eutectic solvent was obtained;

[0078] The low eutectic solvent was subjected to microwave heating at 500 W and 60° C. for 5 min to obtain a carbon quantum dot solution.

[0079] The method for preparing modified activated carbon using the above carbon quantum dots specifically comprises the following steps:

[0080] Step a, adding fly ash from a coal-fired power plant into a mixed acid solution of nitric acid and phosphoric acid in a molar ratio of 1:3, with a solid-liquid ratio of 1 g:10 mL, dispersing evenly, immersing at 120° C. for 5 hours, filtering, washing the filter residue until the pH of the washing solution is 6-7, and drying to obtain an activated carbon raw material; the mass concentration of nitric acid in the mixed acid solution is 68%, and the mass concentration of phosphoric acid is 85%;

[0081] Step b, mixing the above 100 mL carbon quantum dot solution with 15 g of the activated carbon raw material prepared in step a, placing them in a tubular furnace, heating to 800° C., roasting for 2.5 h, purging with nitrogen for 30 min, and cooling to room temperature to obtain modified activated carbon.

[0082] Comparative Example 1

[0083] 0.04 mol (6.12 g) of fumaryl chloride and 0.01 mol (2.70 g) of ferric chloride hexahydrate were placed in a round-bottom flask, placed in an 80°C oil bath, and reacted with magnetic stirring for 2 h, but no uniform transparent liquid could be obtained.

[0084] Even if the temperature is continued to rise to 150°C and the time is extended to 6 hours, a uniform transparent liquid cannot be obtained. In other words, a low eutectic solvent cannot be prepared using fumaryl chloride and ferric chloride hexahydrate as raw materials, and further, the corresponding carbon quantum dots and modified activated carbon cannot be prepared.

[0085] Comparative Example 2

[0086] This comparative example provides a carbon quantum dot and modified activated carbon. The carbon quantum dot is prepared by microwave reaction using a low eutectic solvent prepared by N-[3-(dimethylamino)propyl]lauramide and cupric chloride dihydrate in a molar ratio of 2:1 as a precursor. The specific preparation steps are as follows:

[0087] 0.02 mol (5.69 g) of N-[3-(dimethylamino)propyl]lauramide and 0.01 mol (1.71 g) of cupric chloride dihydrate were mixed and added into a round-bottom flask, and heated at 90° C. for 2 h to obtain a low eutectic solvent.

[0088] The above-mentioned low eutectic solvent was used to prepare modified activated carbon according to the same preparation method as Example 3.

[0089] Comparative Example 3

[0090] This comparative example provides a carbon quantum dot and modified activated carbon. The carbon quantum dot is prepared by microwave reaction using a low eutectic solvent prepared from benzamide and cobalt chloride hexahydrate in a molar ratio of 2:1 as a precursor. The specific preparation steps are as follows:

[0091] 0.02 mol (2.42 g) of benzamide and 0.01 mol (2.38 g) of cobalt chloride hexahydrate were mixed and added into a round-bottom flask, and heated at 90° C. for 2 h to obtain a low eutectic solvent.

[0092] The above-mentioned low eutectic solvent was used to prepare modified activated carbon according to the same preparation method as Example 3.

[0093] Comparative Example 4

[0094] This comparative example provides a modified activated carbon, and its preparation method is exactly the same as that of Example 3, except that the N-[3-(dimethylamino)propyl]lauramide in Example 3 is replaced by an equal amount of acetamide.

[0095] Comparative Example 5

[0096] This comparative example provides an unmodified activated carbon, and the preparation steps are as follows:

[0097] Step a, adding fly ash from a coal-fired power plant into a mixed acid solution of nitric acid and phosphoric acid in a molar ratio of 1:3, with a solid-liquid ratio of 1 g:10 mL, dispersing evenly, immersing at 120° C. for 5 hours, filtering, washing the filter residue until the pH of the washing solution is 6-7, and drying to obtain an activated carbon raw material; the mass concentration of nitric acid in the mixed acid solution is 68%, and the mass concentration of phosphoric acid is 85%;

[0098] Step b, the activated carbon raw materials prepared above are mixed and placed in a tubular furnace, heated to 600° C., roasted for 1.5 h, purged with nitrogen for 25 min, and cooled to room temperature to obtain unmodified activated carbon.

[0099] Performance Testing

[0100] In order to better illustrate the characteristics of the modified activated carbon provided by the embodiments of the present invention, relevant tests were carried out on the modified activated carbon prepared in Examples 1-6, Comparative Examples 2-4, and the unmodified activated carbon in Comparative Example 5, and the test contents included specific surface area, pore size analysis, autoignition point test, and chloroform and nitrogen absorption performance test.

[0101] 1.1 Characterization

[0102] The microscopic morphology of the unmodified activated carbon of Comparative Example 5 and the modified activated carbon of Example 3 was analyzed by scanning electron microscopy. Figure 1 It can be seen that compared with unmodified activated carbon, the activated carbon modified with carbon quantum dots has a richer pore structure.

[0103] The specific surface area and pore size of the modified activated carbon sample prepared in Example 3 were tested by BET. The results showed that the specific surface area of ​​the modified activated carbon prepared in Example 3 can reach 1230.3782 m 2 / g, large and mesoporous volume can reach 0.3194cm3 / g, the micropore volume can reach 0.5630cm 3 / g, the total pore volume can reach 0.8824cm 3 / g, and the pore size distribution is mainly micropores.

[0104] 1.2 Spontaneous combustion performance

[0105] The modified activated carbon adsorbent sample prepared in Example 3 was tested for its auto-ignition point using a solid auto-ignition point analyzer. 1 g of the modified activated carbon was placed in a metal mesh cube with a side length of 20 mm, and the temperature was raised to 400°C at a rate of 0.5°C / min. The test found that the auto-ignition temperature of the modified activated carbon was 384.6°C, and it took 11h52min for the auto-ignition to occur, which was 26.5°C higher than that of the unmodified activated carbon. The ignition time was delayed by nearly an hour, and the safety was significantly improved.

[0106] The modified activated carbon prepared in Example 3 was tested for explosion concentration using a 20L spherical explosion device. An ignition energy of 10KJ was used and 10g / cm 3 The maximum explosion pressure of the modified activated carbon prepared in Example 3 after saturation with chloroform adsorption was 0.45 MPa, and the optimal explosion concentration was 400 g / cm 3 The maximum explosion pressure of the original unmodified activated carbon after saturation with chloroform is 0.59 MPa, and the optimal explosion concentration is 280 g / cm 3 The results show that the maximum explosion pressure of the modified activated carbon after adsorbing chloroform is lower than that of the original activated carbon, and the concentration at which the maximum explosion pressure is reached is increased, indicating that the conditions for the modified activated carbon to reach the maximum explosion pressure are improved compared with the original activated carbon, and the sensitivity to dust concentration is weakened, and the modified activated carbon is safer.

[0107] 1.3 Adsorption performance

[0108] The modified activated carbon prepared in Examples 1-6, Comparative Examples 2-4 and the unmodified activated carbon sample of Comparative Example 5 were tested for their absorption performance of chloroform. The activated carbon adsorption of chloroform vapor experiment was carried out using an online adsorption device. The system mainly includes an online catalyst evaluation device, a gas chromatograph and a high-pressure constant current pump. The chloroform liquid was quantitatively pumped into the vaporizer in the catalyst online evaluation device by a high-pressure constant current pump, and the vaporization temperature was set to 100°C. After the chloroform liquid was completely vaporized and the temperature of the vaporizer was kept constant for 0.5h, the high-pressure constant current pump switch was turned on to carry out the adsorption experiment in the adsorption column. The temperature of the adsorption column was set to 80°C, the reaction step length was 4min, and the peak area was recorded every 4min. When the adsorption reached dynamic equilibrium, the peak area fluctuated up and down at a certain value. When adsorption saturation was reached, the saturated adsorption amount of chloroform was calculated based on the mass difference of the activated carbon in the adsorption column before and after adsorption.

[0109] Q=(m0-m1) / m0×1000

[0110] Where:

[0111] Q—unit activated carbon adsorption of chloroform vapor saturated adsorption, mg / g;

[0112] m0—mass of adsorption column, g;

[0113] m1—mass of the adsorption column after adsorption, g;

[0114] Table 1

[0115] Saturated adsorption capacity (mg / g) Saturated adsorption time (min) Example 1 675.57 64 Example 2 641.64 58 Example 3 743.75 47 Example 4 581.58 83 Example 5 502.97 92 Example 6 462.91 115 Comparative Example 2 408.62 80 Comparative Example 3 348.44 94 Comparative Example 4 370.84 67 Comparative Example 5 280.76 166

[0116] The modified activated carbon prepared in Example 3 was subjected to a nitrogen adsorption test in the same manner as above to examine the selectivity of the adsorbent. The adsorption amount was 6.47 mg / g, and the selectivity of chloroform / N2 was calculated to be 115:1.

[0117] The modified activated carbon prepared in Example 3 was subjected to a carbon dioxide adsorption test in the same manner as above to examine the selectivity of the adsorbent. The adsorption amount was 10.62 mg / g, and the selectivity of chloroform / carbon dioxide was calculated to be 70:1.

[0118] 1.4 Reusability

[0119] Take the modified activated carbon that has been saturated with adsorption in Example 1, put it in a closed container, and vacuum treat it at 80°C for 3 hours to complete the regeneration of the modified activated carbon. The regenerated modified activated carbon is subjected to adsorption experiment again according to the above method, and the experiment is repeated 5 times.

[0120] After being reused 5 times, the saturated adsorption capacity of chloroform by the modified activated carbon was 735.54 mg / g, the selectivity of chloroform / N2 was 278:1, and the selectivity of chloroform / carbon dioxide was 69:1.

[0121] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A carbon quantum dot, characterized in that The low eutectic solvent prepared from an amide compound and a transition metal compound is used as a precursor and prepared by a microwave heating method; Wherein, the molar ratio of the amide compound to the transition metal compound is 6:1 to 1:2; The amide compound is at least one of fumaramide, N,N-diethyl lauramide or N-[3-(dimethylamino)propyl] lauramide; and the transition metal compound is an oxide or salt of Fe, Ni or Co.

2. The carbon quantum dot according to claim 1, characterized in that The transition metal compound is at least one of ferric chloride hexahydrate, ferric oxide, nickel chloride hexahydrate, nickel oxide, cobalt chloride hexahydrate or cobalt monoxide.

3. The carbon quantum dots according to claim 1, characterized in that The preparation method of the low eutectic solvent is as follows: the amide compound and the transition metal compound are uniformly mixed, heated to 50° C. to 120° C., and the temperature is kept constant until the system is uniform and transparent, so as to obtain the low eutectic solvent.

4. A method for preparing carbon quantum dots according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: subjecting the low eutectic solvent to microwave heating reaction to obtain a carbon quantum dot solution.

5. The method for preparing carbon quantum dots according to claim 4, characterized in that: The microwave heating reaction has a power of 500W to 800W, a temperature of 50°C to 70°C, and a time of 3min to 8min.

6. A modified activated carbon, characterized in that: The invention comprises the carbon quantum dots and activated carbon as described in any one of claims 1 to 3.

7. A method for preparing modified activated carbon according to claim 6, characterized in that: The method comprises the following steps: uniformly mixing activated carbon raw materials and carbon quantum dot solution, and calcining them under an inert atmosphere to obtain modified activated carbon.

8. The method for preparing modified activated carbon according to claim 7, characterized in that: The activated carbon raw material is fly ash residue obtained by acid leaching and impurity removal of fly ash from a coal-fired power plant; and / or The calcination temperature is 600°C to 1000°C, and the calcination time is 1h to 4h; and / or The mass-to-volume ratio of the activated carbon raw material to the carbon quantum dot solution is 5-20:100, wherein the unit of mass is gram and the unit of volume is milliliter.

9. The method for preparing modified activated carbon according to claim 7, characterized in that: The preparation method of the activated carbon raw material comprises the following steps: adding fly ash from a coal-fired power plant into a mixed acid solution, dispersing the mixture evenly, soaking the mixture at 120° C. to 130° C. for 3 h to 6 h, filtering, washing the filter residue, and drying the mixture to obtain the activated carbon raw material.

10. Use of the modified activated carbon according to claim 6 or the modified activated carbon prepared by the preparation method according to any one of claims 7 to 9 in adsorbing industrial CVOCs waste gas.

Citation Information

Patent Citations

  • Organic functional luminescent carbon quantum dots, preparation method therefor and applications thereof

    CN103421495A

  • Energy-containing eutectic solvent, application thereof, metal doped carbon quantum dots prepared from energy-containing eutectic solvent, and preparation method of metal doped carbon quantum dots

    CN110550616A